1392 Challenges of Heart Surgery on A Patient with Anorexia Nervosa: A Rare Case Report of The Perilous Effects on The Myocardium. (12th October 2021) - Ashraf, M; Zargaran, D; Lucchese, G; Bosco, P
Abstract: This peculiar case highlights the detrimental effects of Anorexia Nervosa (AN) on myocardial tissue, and the significant impact this can have on surgical outcome. A 49-year-old female with history of AN presented acutely unwell with confusion, dizziness, deranged electrolytes and metabolic acidosis. She had lost significant weight in the past month with suspected laxative abuse. She required intubation due to extensive bilateral pulmonary effusions and multiple organ failure. Echocardiogram showed appearance of a rheumatic mitral valve with severe stenosis, a mean gradient of 16mmHg and moderate regurgitation. Urgent surgical intervention to replace the valve was indicated. Following replacement of the mitral valve, torrential bleeding ensued after coming off bypass. This had resulted from a dramatic atrio-ventricular dissociation. Attempts to repair the deficit were hampered by extremely fragile myocardial tissue. Unfortunately, despite extensive efforts to repair the damage and control bleeding, it was ultimately in vain. Histology of the myocardium in AN patient has revealed evidence of diffuse endocardial and interstitial fibrosis and myxoid material deposition. This case is the first to illustrate the sequelae of AN on myocardial tissue with its subsequent peri-operative impact. Before surgical intervention we suggest that maximal efforts to optimize nutrition should be undertaken pre-operatively, seeking to reverse the structural changes caused by AN. This case highlights the need for further exploration of the effects that a patient's nutritional status can have on the quality of tissue being operated on.